Dengue and dengue hemorrhagic fever in the Americas : guidelines for prevention and control (PAHO WashingtonUS, 1994)
Stresses a comprehensive vector control effort that brings together all posssible safe, effective, and economical control methods to keep vector populations at acceptable levels. Underscores the importance of environmental management.
DC